PROBLEMATIKA DAN PERUBAHAN KURIKULUM PENDIDIKAN YANG KERAP KALI MENGALAMI PERUBAHAN DI SETIAP TAHUNNYA - Adistya Shofia Finanda; Jihan Fira Fadhila; Hayat, Hayat (Bajang Institute, 2024)
In the context of education, curriculum changes are often faced with diverse challenges. These include global demands, technological developments, and dynamic community needs. This research aims to analyze the problems that arise due to curriculum changes that occur every year, as well as their impact on the learning process and student competence. In addition, it aims to create students who are broad-minded, creative, critical, and innovative towards the problems that will be faced in the future. The method used in this research is a literature study and a survey of educators and students to identify gaps between curriculum policy and its implementation in the field. The conclusion of this study shows that although curriculum changes aim to improve the quality of education, often rapid and poorly planned changes result in learning difficulties and instability in the teaching and learning process, requiring a more structured and participatory approach to its design.